DESAIN MODEL PEMBELAJARAN DENGAN MODEL KOOPERATIF TIPE THINK PAIR SHARE DAN PENDEKATAN ILMIAH TERHADAP KEMAMPUAN SISWA DALAM PEMAHAMAN KONSEP DAN PEMECAHAN MASALAH PADA MATERI PROGRAM LINEAR DI KELAS XI SMA NEGERI 1 SUNGGAL - Ivan Pernando (Jurnal Visi Eksakta, 2024)
This research uses quasi-experimental research. The population in this study were students of Class XI MIPA at SMA Negeri 1 Sunggal T.P. 2019/2020. This research aims to make it easier for students to achieve learning goals in understanding concepts and solving linear programming problems using a Think Pair Share (TPS) type cooperative model and a scientific approach. The research results show that the learning model that has been designed is good for use. The tcount value for the problem solving test is 5.0350 while ttable = 1.667, which means tcount > ttable, meaning it is accepted or rejected, so it is concluded that learning using the think pair share type cooperative model is better than the scientific approach to linear programming problem solving in Class XI Sunggal 1 Public High School T.P. 2019/2020. Keywords: Cooperative Think Pair Share Type, Scientific Approach, Concept Understanding